Phase angle as an indicator of body composition and physical performance in handball players - Silvino, V. O.; Barros, K. R. B.; Brito, F. M.; Magalhães, F. M. D.; Carioca, A. A. F.; Loureiro, A. C. C.; Veras-Silva, A. S.; Drummond, M. D. M.; Santos, M. A. P. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Phase angle (PhA), obtained from the bioimpedance analysis, is widely used in clinical situations and in sports. This study evaluated the association between PhA with body composition and physical performance of handball athletes.